γδ T cell-mediated cytotoxicity against patient-derived healthy and cancer cervical organoids - Dong, Junxue; Holthaus, David; Peters, Christian; Koster, Stefanie; Ehsani, Marzieh; Quevedo-Olmos, Alvaro; Berger, Hilmar; Zarobkiewicz, Michal; Mangler, Mandy; Gurumurthy, Rajendra Kumar; Hedemann, Nina; Chumduri, Cindrilla; et al. (Frontiers in Immunology, 2023)
Cervical cancer is a leading cause of death among women globally, primarily driven by high-risk papillomaviruses. However, the effectiveness of chemotherapy is limited, underscoring the potential of personalized immunotherapies. Patient-derived organoids, which possess cellular heterogeneity, proper epithelial architecture and functionality, and long-term propagation capabilities offer a promising platform for developing viable strategies. In addition to αβ T cells and natural killer (NK) cells, γδ T cells represent an immune cell population with significant therapeutic potential against both hematologic and solid tumours. To evaluate the efficacy of γδ T cells in cervical cancer treatment, we generated patient-derived healthy and cancer ectocervical organoids. Furthermore, we examined transformed healthy organoids, expressing HPV16 oncogenes E6 and E7. We analysed the effector function of in vitro expanded γδ T cells upon co-culture with organoids. Our findings demonstrated that healthy cervical organoids were less susceptible to γδ T cell-mediated cytotoxicity compared to HPV-transformed organoids and cancerous organoids. To identify the underlying pathways involved in this observed cytotoxicity, we performed bulk-RNA sequencing on the organoid lines, revealing differences in DNA-damage and cell cycle checkpoint pathways, as well as transcription of potential γδ T cell ligands. We validated these results using immunoblotting and flow cytometry. We also demonstrated the involvement of BTN3A1 and BTN2A1, crucial molecules for γδ T cell activation, as well as differential expression of PDL1/CD274 in cancer, E6/E7+ and healthy organoids. Interestingly, we observed a significant reduction in cytotoxicity upon blocking MSH2, a protein involved in DNA mismatch-repair. In summary, we established a co-culture system of γδ T cells with cervical cancer organoids, providing a novel in vitro model to optimize innovative patient-specific immunotherapies for cervical cancer.